Sosialisasi dan Pelatihan Pengelolaan Keuangan Kas Pada PJJ Sektor 1 Gereja Batak Karo Protestan Runggun Padang Cermin - Merry Moy Mita; Supriadi Siagian (CV. Armas Suan Sejahtera, 2025)
This community service activity aims to provide knowledge and guidance to the congregation, especially PJJ Sector 1 GBKP Runggun Padang Cermin, Langkat Regency, North Sumatra, regarding how to prepare cash financial reports. This activity was carried out on June 6-7, 2025 at the home of one of the administrators of PJJ Sector 1 GBKP Runggun Padang Cermin, Langkat Regency. The delivery method in this training is divided into five, namely interactive presentations, group discussions, exercises or stimulation, real case studies, and Q&A sessions. This activity is divided into two days with the agenda on the first day focusing on discussing building the foundations of cash management, and on the second day the focus of the discussion is cash planning and control. The result of this activity is an increase in the knowledge of the congregation of PJJ Sector 1 Runggun Padang Cermin, Langkat Regency regarding proper cash financial management. The congregation, especially the administrators, learn to make financial reports quickly and regularly